Deep tissue injury: a narrative review on the aetiology of a controversial wound. (11th March 2021) - Wynn, Matthew
Abstract : Deep tissue injuries (DTIs) were added to pressure ulcer grading systems in 2009. Since then, they have been associated with the same aetiological processes as other forms of pressure injury (PI). This is despite notable clinical differences in their presentation along with variations in natural history that suggest they are the consequence of processes distinct from those that cause other PIs. Understanding the aetiology of DTIs is essential to guide prevention and treatment in addition to ensuring healthcare governance processes deeply tied to pressure injury are effective and efficient. Current understanding of the aetiology of DTI has significant gaps, with several key challenges impeding progress in this area of PI research, including inconsistent reporting by healthcare services and the limitations of animal and computer models in addition to the ethical barriers to conducting studies on human subjects. Synthesis of early studies with studies undertaken before 2009 is also limited by the variety in definitions of DTI used before that published by the European Pressure Ulcer Advisory Panel, the National Pressure Injury Advisory Panel and the Pan Pacific Pressure Injury Alliance in 2009. To date, few prospective clinical studies have been conducted. This article presents a narrative review on the clinical and animal study evidence indicating contemporary understanding of DTI.